The Jesuits: cultures, sciences, and the arts, 1540-1773 - O'Malley, John W. (University of Toronto Press, 1999)
"In recent years scholars in a range of disciplines have begun to re-evaluate the history of the Society of Jesus. Approaching the subject with new questions and methods, they have reconsidered the importance of the Society in many sectors, including those related to the sciences and the arts. They have also looked at the Jesuits as emblematic of certain traits of early modern Europeans, especially as those Europeans interacted with 'the Other' in Asia and the Americas." "Originating in an international conference held at Boston College in 1997, the thirty-five essays here reflect this new historiographical trend."--BOOK JACKET